국내 소프트 타깃 대상 드론테러의 법제도 개선방안 연구 - 오한길; Oh, Hangil (한국재난정보학회 논문집, 15(1), 2019)
Purpose: This study aims to apply the counter terrorism policy in pertain to malicious drone abuse and the croweded public places in South Korea. And, to improve counter terrorism protection measure, this study suggests an adoptation of Anti UAV technology into counter terrorism related regulation. Method: Compared to nations' operations of counter terrorism prevention and protection activities with the South Korean gov, problems and limitations are suggested. Results: Anti UAV technology could not be applied for Multi-user facilities by any law due to the limitation, so that it is required to amend counte terrporism related policies and law. Conclusion: This study intends to identify various protection methods against UAV threats. To reduce the risk of UAV, the law of public safety and counter terrorism should be promoted and reinforced for the first. 연구목적: 본 연구는 드론의 테러위협으로부터 민간 다중이용시설이 안전하고 유익하게 사용될 수 있도록, 민간시설의 드론테러 방어를 위한 법제도의 개선방안을 제시하고자 한다. 연구방법:연구를 위해 국가가 민간시설에 대해 시행하고 있는 대테러활동 운영실태를 조사 분석하였으며, 국외의 모범사례를 기술하고 비교하여 국내에 필요한 드론테러에 대한 국가 대테러정책의 방향을 제시하고 있다. 연구 결과: 국내 드론테러에 대한 법제도 한계점에 대하여 연구한 결과, 국내 적용 가능한 안티드론 기술을 구축 활용하기 어려워짐에 따라 드론테러에 대한 위협 뿐만 아니라, 사생활 침해, 스토킹 등의 범죄에도 취약점이 드러났다. "전파법과" 정보보호관련 법률 등 국민의 안전에 관한 법률은 안티드론기술의 도입을 방해하는 장애요인이 되고 있으므로 본 논문에서 제시하고 있는 법제도의 개선이 요구된다. 결론: 본 연구를 통해 민간시설 드론테러 취약요인과 피해경감대책의 법제도적 한계점과 개선방안을 하였다. 따라서 본 연구의 개선방안을 검토하여 드론테러의 대책방안이 마련되어야 한다.